An alliance between chiral phosphite-type compounds and porphyrins in asymmetric palladium catalysis. (1st December 2016) - Gavrilov, Konstantin N.; Zheglov, Sergey V.; Maksimova, Marina G.; Mikhel, Igor S.
GRAPHICAL ABSTRACT: ABSTRACT: Some novel results obtained at the confluence of organophosphorus and porphyrin chemistry are briefly overviewed. The focus is put on the P * -chiral porphyrin-appended diamidophosphite ligands as well as achiral metalloporphyrins used in Pd-catalyzed asymmetric allylation.